Perencanaan Sistem Jaringan Distribusi Air Bersih di Desa Jonjo Kecamatan Parigi - Ade Fajar Sidiq; Sukmasari Antaria; Andi Bunga Tongeng (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Parigi Sub-district in Jonjo Village, Gowa Regency, faces challenges in the availability of clean water, just like other areas. Local communities often experience difficulties in accessing safe and quality clean water. Geographical conditions are the main obstacle in the distribution of clean water in this area. Therefore, careful planning of the clean water distribution network system is needed to meet the needs of residents and overcome the existing obstacles. This study aims to calculate the clean water needs of the Jonjo Village community, Parigi Subdistrict in 2040, and design a clean water distribution network system using EPANET 2.0 software. The results showed that the average demand for clean water in 2040 was estimated to reach 5,780 liters per second, with peak hour demand reaching 9,017 liters per second. Based on the analysis with EPANET 2.0, a network scheme was designed that includes 1 reservoir unit, 23,093 meters of pipelines with various diameters which are 114 mm, 89 mm, and 60 mm, and is equipped with 1 pressure release basin.